Augmenting mobile 3G using WiFi - Balasubramanian, Aruna; Mahajan, Ratul; Venkataramani, Arun (MobiSys'10, San Francisco, California, USA., 2010)
We investigate if WiFi access can be used to augment 3G capacity in mobile environments. We first conduct a detailed study of 3G and WiFi access from moving vehicles, in three diff erent cities. We find that the average 3G and WiFi availability across the cities is 87% and 11%, respectively. WiFi throughput is lower than 3G throughput, and WiFi loss rates are higher. We then design a system, called Wiffler, to augments mobile 3G capacity. It uses two key idea leveraging delay tolerance and fast switching|to overcome the poor availability and performance of WiFi. For delay tolerant applications, Wier uses a simple model of the environment to predict WiFi connectivity. It uses these predictions to delays transfers to offload more data on WiFi, but only if delaying reduces 3G usage and the transfers can be completed within the application's tolerance threshold. For applications that are extremely sensitive to delay or loss (e.g., VoIP), Wiffler quickly switches to 3G if WiFi is unable to successfully transmit the packet within a small time window. We implement and deploy Wiffler in our vehicular testbed. Our experiments show that Wiffler signi cantly reduces 3G usage. For a realistic workload, the reduction is 45% for a delay tolerance of 60 seconds.